Implementation of Contextual Teaching and Learning and Authentic Assessments to the Science (IPA) Learning Outcomes of 4th Grade Students of Primary Schools (SD) in Kota Kupang - Uslan, Uslan; Muhsam, Julhidayat; Hasyda, Suryadin; Aiman, Ummu (Journal of Education Research and Evaluation, 2021)
This study aims to discover the implementation of CTL and authentic assessment to the science learning outcomes on 4th-grade students of primary school in Kota Kupang. This study is quasi-experimental using a 2 x 2 factorial design. There are 110 students as the population, in which 60 students are appointed as the samples thru a random sampling technique. Data collection uses an objective test method. The data are analyzed using one-way ANOVA and two-way ANOVA that is followed by t-Scheffe test. The results of this study indicate that: (1) there is a difference of learning outcomes between the students who attend the CTL with the conventional learning, (2) there is a difference on the students’ learning outcomes who attend the performance assessment with the project assessment, (3) there is an influence of interaction between the learning model and assessment used to the learning outcomes, (4) there is difference of the students’ learning outcomes who attend the CTL, in which it is between the students who attend the performance assessment and the students who attend the project assessment, (5) there is a difference of learning outcomes on the students who attend the conventional learning, in which it is between the students who attend the performance assessment and the students who attend the project assessment, (6) there is a difference of learning outcomes on the students who attend the performance assessment, in which it is between the students who attend the CTL and conventional learning, and (7) there is a difference of learning outcomes on the students who attend the project assessment, in which it is between the students who attend the CTL and the students who attend the conventional learning. Hence, the implementation of CTL and authentic assessments toward the science learning outcomes of 4th-grade students of primary school in Kota Kupang.